Hey ...!
Answer this !
Simplify (2x+p-c)^2-(2x-p+c)^2
Thanks :)
Answers
Answered by
7
Hey there!
Kindly refer to the following attached paper for a detailed process and the final answer to this query that is,
![\boxed{\bf{\underline{8xp - 8xc}}} \boxed{\bf{\underline{8xp - 8xc}}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cbf%7B%5Cunderline%7B8xp+-+8xc%7D%7D%7D)
Hope this helps and solves the digits for expansion for two expressions!!!!
Kindly refer to the following attached paper for a detailed process and the final answer to this query that is,
Hope this helps and solves the digits for expansion for two expressions!!!!
Attachments:
![](https://hi-static.z-dn.net/files/d46/9b5414e234df86ebffb7209f948256b3.jpg)
Anjula:
Thanks a lottt yarr ..
Answered by
1
evalute:(2×+p-c)×2
= 4×2+4xp-4xc+p2-2pc+can
evalute:(2x-p+c)2x
=4x2-4xp+4xc+p2-2pc+can
now, pull out like factors .
=8xp-(p-c)
=8x•(p-c)
= 4×2+4xp-4xc+p2-2pc+can
evalute:(2x-p+c)2x
=4x2-4xp+4xc+p2-2pc+can
now, pull out like factors .
=8xp-(p-c)
=8x•(p-c)
Similar questions